Imaging progressive peripheral and central dysfunction in isolated REM sleep behaviour disorder after 3 years of follow-up. (August 2022) - Fedorova, Tatyana D.; Knudsen, Karoline; Andersen, Katrine B.; Horsager, Jacob; Skjærbæk, Casper; Beier, Christoph P.; Sommerauer, Michael; Svendsen, Kristina B.; Otto, Marit; Borghammer, Per
Abstract: Introduction: Most patients with isolated rapid eye movement sleep behaviour disorder (iRBD) convert to Parkinson's disease (PD), dementia with Lewy bodies, or multiple system atrophy within 15 years of diagnosis. Furthermore, iRBD patients develop non-motor symptoms similar to those of manifest PD patients and display dysfunction of the sympathetic and parasympathetic nervous system, comparable to that seen in PD. However, progression rates of autonomic dysfunction in iRBD have not been studied with objective measures in detail, which is the aim of this study. Methods: Twenty-two iRBD patients were included at baseline and 14 participated in follow-up after 3 years. Colonic transit time (CTT) was examined using radio opaque markers, colonic volume was defined on abdominal computed tomography (CT) scans, Iodine-123-metaiodobenzylguanidine ([123I]MIBG) scintigraphy was performed to assess cardiac sympathetic innervation, and 3, 4-dihydroxy-6-(18F) fluoro-l -phenylalanine ([18F]FDOPA) positron emission tomography (PET) scan determined nigrostriatal dopamine storage capacity. All examinations were performed at baseline and after 3 years. Results: iRBD patients displayed increased CTT (p = 0.001) and colonic volume (p = 0.01) at follow-up compared to baseline. Furthermore, [123I]MIBG uptake and [18F]FDOPA uptake showed progressive reductions at follow-up (p = 0.02 and p = 0.002, respectively). No correlations were seen between changes in intestinal or cardiac measurements and dopaminergic function. Conclusion: Using objective markers, the present study documented that intestinal dysfunction and cardiac sympathetic degeneration worsen in the majority of iRBD patients over a 3-year period. The absent correlation between these markers and nigrostriatal dopaminergic dysfunction suggests that progressive gastrointestinal and cardiac dysfunction in iRBD is caused mainly by non-dopaminergic mechanisms. Highlights: Non motor manifestations in REM sleep behavior disorder progress over time. Simple imaging techniques capture progression of REM sleep behavior disorder. Mapping of gradual progression from REM sleep behavior disorder to parkinsonism.